Tinjauan Hukum Tentang Hibah Dan Batasan Pemberian Hibah - Aris Priyadi (Wijayakusuma Law Review, 2023)
Abstract A grant is a gift from one person to another where the giver is still alive. Materially, the existence of a grant has something to do with inheritance. Provisions/rules regarding grants in Indonesia are still pluralistic. Basically, an owner of property has the right and freedom to give/grant to anyone, including his children, provided that the gift (grant) does not cover and does not reduce other rights as heirs. If the conditions and pillars are met then the grant is valid. Giving grants according to Islamic law (Compilation of Islamic Law) is limited to a maximum of 1/3 (one third) of the total assets of the grantor. In the event that grants are made to their children (heirs), then the limitation is that grants must be made with the principle of justice. This grant limit is given to protect the rights of the heirs after the grantor dies. In addition to the maximum limits regulated in the Compilation of Islamic Law (KHI), customary law and the Civil Code also provide the same limits on grant grants. This is intended to protect the absolute rights of the heirs and to avoid losses suffered by the heirs whose share cannot be reduced according to law (legitieme portie). Keywords: Grants, conditions, restrictions Abstrak Hibah merupakan pemberian seseorang kepada orang lain dimana sipemberi tersebut masih dalamkeadaan hidup. Secara materiil, eksistensi hibah ada hubunganya dengan kewarisan. Ketntuan/aturan tentang hibah di Indonesia sampai saat ini masih bersifat pluralistis. Pada dasarnya seorang pemilik harta kekayaan berhak dan leluasa memberikan/menghibahkan kepada siapapun, termasuk pula kepada anaknya dengan syarat pemberian (hibah) tersebut tidak menutup dan tidak mengurangi hak-hak yang lain sebagai ahli waris. Apabila syarat dan rukunnya terpenuhi maka hibah tersebut adalah sah. Pemberian hibah menurut hukum Islam (Kompilasi Hukum Islam) dibatasi maksimal 1/3 (sepertiga)dari keseluruhan harta pemberi hibah. Dalamhal pemberian hibah dilakukan kepada anak-anaknya (ahli waris),maka batasannya adalah penghibahan harus dilakukan dengan prinsip keadilan. Batasan pemberian hibah ini diberikan untuk melindungi hak-hak para ahli waris setelah pemberi hibah meninggaldunia. Selain batasan maksimal yang diatur dalam Kompilasi Hukum Islam (KHI) , hukum adat dan KUHPerdata juga memberikan batasan yang sama dalam pemberian hibah. Hal ini dimaksudkan untuk melindungi hak-hak mutlak para ahli waris dan untuk menghindari kerugian yang diderita oleh para ahli waris yang menurut undang-undang bagiannya tidak boleh dikurangi (legitieme portie). Kata kunci: Hibah, ketentuan, pembatasan